MIMO Fading Emulator Development with FPGA and Its Application to Performance Evaluation of Mobile Radio Systems - Yoshio Karasawa; Katsuhiro Nakada; Guijiang Sun; Rikako Kotani (International Journal of Antennas and Propagation)
We present four new developments for a multiple-input multiple-output (MIMO) over-the-air measurement system based on our previous studies. The first two developments relate to the channel model for multipath environment generation. One is a further simplification of the circuit configuration without performance degradation by reducing the number of delay generation units, which dominate the performance limit when implementing the circuit on a field-programmable gate array (FPGA). The other is to realize spatial correlation characteristics among the input ports on the transmission side, whereas the previously proposed channel model did not consider this correlation. The third development involves the details of implementing the MIMO fading emulator on an FPGA as a two-stage scheme. The fourth is the demonstration of application examples of the developed system.